2016
DOI: 10.4102/ojvr.v83i1.1172
|View full text |Cite
|
Sign up to set email alerts
|

An update of the tsetse fly (Diptera: Glossinidae) distribution and African animal trypanosomosis prevalence in north-eastern KwaZulu-Natal, South Africa

Abstract: An unpredicted outbreak of African animal trypanosomosis or nagana in 1990 in north-eastern KwaZulu-Natal necessitated an emergency control programme, utilising the extensive cattle-dipping system in the area, as well as a reassessment of the tsetse and trypanosomosis problem in the province. Since 1990, sporadic blood sampling of cattle at the dip tanks in the nagana-infested areas were undertaken to identify trypanosome species involved and to determine the infection prevalence in cattle. The distribution an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 23 publications
(36 reference statements)
1
20
1
Order By: Relevance
“…Two tsetse species, Glossina brevipalpis and G. austeni, are present in an area of 16,000 km 2 in the north eastern part of the KwaZulu-Natal Province in South Africa [39,40], and both populations extend into southern Mozambique and G. austeni into eSwatini [41][42][43]. Although G. austeni is considered to be the more competent vector for the transmission of Trypanosoma parasites, it has been shown that both species can transmit Trypanosoma congolense and Trypanosoma vivax in South Africa [44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…Two tsetse species, Glossina brevipalpis and G. austeni, are present in an area of 16,000 km 2 in the north eastern part of the KwaZulu-Natal Province in South Africa [39,40], and both populations extend into southern Mozambique and G. austeni into eSwatini [41][42][43]. Although G. austeni is considered to be the more competent vector for the transmission of Trypanosoma parasites, it has been shown that both species can transmit Trypanosoma congolense and Trypanosoma vivax in South Africa [44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…In South Africa, Glossina brevipalpis Newstead and Glossina austeni Newstead are the vectors of Trypanosoma congolense and Trypanosoma vivax [47] that cause AAT in an area of about 16 000 km 2 in the north eastern parts of the KwaZulu-Natal Province [8,9]. Because of the limited options available for controlling the parasite, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…brevipalpis extends from Ethiopia in the north to KwaZulu-Natal, South Africa in the south and is present in Somalia, Uganda, Kenya, Rwanda, Burundi, Tanzania, Malawi, Zambia, Zimbabwe and Mozambique [38]. Although this species belongs to the fusca group of tsetse flies, considered of less or no epidemiological importance for livestock, it was recently shown that the role of this species in transmitting AAT in South Africa should not be underestimated [9]. It has become evident that removing only G .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ever since the successful and sustainable eradication of a Glossina pallidipes Austen population from Zululand in the 1950’s, the two remaining tsetse species Glossina brevipalpis Newstead and Glossina austeni Newstead have always been considered of minor epidemiological importance [3–7]. The outbreak of nagana in 1990 showed that this assumption was a fallacy [8]. …”
Section: Introductionmentioning
confidence: 99%